Management practices and productivity in Germany - Sandra Broszeit; Ursula Fritsch; Holger Görg; Marie-Christine Laible (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
Based on a novel dataset, the "German Management and Organizational Practices" (GMOP) Survey, we calculate establishment specific management scores following Bloom and van Reenen as indicators of management quality. We find substantial heterogeneity in management practices across establishments in Germany, with small firms having lower scores than large firms on average. We show a robust positive and economically important association between the management score and establishment level productivity in Germany. This association increases with firm size. Comparison to a similar survey in the US indicates that the average management score is lower in Germany than in the US. Overall, our results point towards lower management scores being at least in part to blame for the differences in aggregate productivity between Germany and the US. – – Basierend auf Daten der Studie "German Management and Organizational Practices" (GMOP) werden betriebsspezifische Management-Scores berechnet, welche als Indikator für die Managementqualität in deutschen Betrieben interpretiert werden können. Es zeigen sich substantielle Unterschiede in der Nutzung von Managementpraktiken, wobei kleine Betriebe im Durchschnitt niedrigere Scores aufweisen als große Betriebe. Multivariate Analysen zeigen, dass es einen positiven Zusammenhang zwischen dem Management-Score eines Betriebs und dessen Produktivität gibt, welcher mit der Firmengröße ansteigt. Ein Vergleich mit ähnlichen, amerikanischen Daten ergibt, dass der durchschnittliche Management-Score in Deutschland niedriger ist als in den USA. Wir sehen darin zum Teil die Erklärung für bestehende Produktivitätsunterschiede zwischen Deutschland und den USA.
Keywords: D24; L2; M2; 330; management practices; firm performance; labor productivity; MOPS